TEACHER’S CONSIDERATIONS IN SELECTING TEXTBOOK - Putri, Pramitha; Ikhsanudin, Ikhsanudin; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTextbook selection process takes a crucial part in teaching and learning process. The textbook affects the teaching and learning process, in turn will influence the students’ competencies. Moreover English subject is the only way for the students to learn English, since English is a foreign language which means, students do not use it fluently and intensively. So, textbook determines the result of the teaching and learning process itself. This study presents the textbook selection process and the teacher’s considerations when selecting the textbook. This is a case study research. The participant in this study was an English teacher of Madrasah Tsanawiyah Swasta (MTs) Aswaja Pontanak, one of private Islamic junior high school in Pontianak. The data of this study were collected through observation method and interviews. The research findings revealed that one aspect, besides the teacher, actually took a part and influenced the textbook selection process. This aspect is the involvment of the higher authority of the school. Also, there were some coniderations that the teacher has in selecting the textbook. These consderations are the content of the textbook must follow the most recent curriculum, and the textbook design. Keywords: English Textbook, Textbook Selection, Teacher’s Consideration